PENGASAPAN IKAN MENGUNAKAN LEMARI ASAP SKALA RUMAH TANGGA - Fauzi, M; Ahmad, Muchtar (Fakultas Perikanan dan Kelautan Universitas Riau, 2011)
Experiment on designing of smoking cabinet technology to producedsmoked-fish for cottage scale aquaindustry and to evaluate produced smoked fishorganoleptic and coast have been done. The result shows that small and middlescales smoking fish designed well accountable functionally to produced smokedfish, that caught from marine and fresh waters and cultured fish. Organolepticallythe smoked fish well consumed by the panelists, with value in between 60%-70%depend on the species of smoked fish. The cost of smoked fish produced similarto the market price of smoked fish produced traditionally, the production cost offish materials used alone approximately 73% of market price. This situation opensthe opportunity to improve efficiency of design, engineering and technique ofsmoking.